2021
DOI: 10.21203/rs.3.rs-263301/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The molecular basis for SARS-CoV-2 recognized by dog ACE2

Abstract: SARS-CoV-2 can infect many domestic animals, including dogs. Herein, we show that dog angiotensin converting enzyme 2 (dACE2) can bind to SARS-CoV-2 spike (S) protein receptor binding region (RBD), and that both pseudotyped and authentic SARS-CoV-2 can infect dACE2-expressing cells. we solved the crystal structure of RBD in complex with dACE2 and found that the total numbers of contact residues, contact atoms, hydrogen bonds and salt bridges at the binding interface in this complex are slightly fewer than thos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…In the other hand, in vitro studies have reported that N501Y mutation found in several variants such as Alpha (B.1.1.7), Gamma (P.1) and Delta (B.1.617.2) enhances the a nity of RBD towards dACE2, accounting for a 3-fold increase in a nity (K D =37.1). Hence, wild-type RBD (K D =123nM), augmented a nity and higher viral loads found in lineages carrying D614G mutation that was found in the present study, and it could cause an increase in human-to-animal transmission 22,24 .…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…In the other hand, in vitro studies have reported that N501Y mutation found in several variants such as Alpha (B.1.1.7), Gamma (P.1) and Delta (B.1.617.2) enhances the a nity of RBD towards dACE2, accounting for a 3-fold increase in a nity (K D =37.1). Hence, wild-type RBD (K D =123nM), augmented a nity and higher viral loads found in lineages carrying D614G mutation that was found in the present study, and it could cause an increase in human-to-animal transmission 22,24 .…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, it is important to emphasize that mutation D164G confers increased transmissibility to SARS-CoV-2 by stabilizing Spike protein, this prevents the S1 and S2 segments to be cleaved before RBD interacts with ACE2 receptor 23 . This could be associated with the greater a nity observed by Zhang et al 24 towards dog ACE2 (dACE2) of variants carrying D614G mutation when compared to Wu-1 SARS-CoV-2. Therefore, mutation D614G could play a key role for anthropozoonotic transmission of SARS-CoV-2 24 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Another three important variants of interest (VOIs), Epsilon (B.1.429 lineage), Eta (B.1.525 lineage) and Kappa (B.1.617.1 lineages), were also included. SARS-CoV-2 Wild type strain (Wuhan-1 reference strain) was tested for comparison 16,17 . The mutation site of each variant in spike was listed in Supplementary Fig.…”
Section: Figurementioning
confidence: 99%